An eco-friendly concrete blends from palm oil boiler ash / Nurrul Amilin Zainal Abidin ... [et al.] - Zainal Abidin, Nurrul Amilin; Michael, Zeno; Mohamed Yusof, Mohamed Khatif Tawaf; Roslan, Azmi; Sharipudin, Siti Shahidah; Mohammad, Shahrul Nizam; Shahrul Azhar, Ilya Izyan (2021)
Palm Oil Boiler Ash (POBA) is a subsequent by-product obtained from the combustion of fibers and kernel shells in palm oil mill boiler, abundantly available and often wasted without further usage. Utilising these materials in lightweight concrete blends offers a great opportunity, especially in addressing environmental issues. The replacement of natural sand and cement with 5% POBA by weight contributes to the highest and favourable compressive strength of the concrete. The compressive strength increases as the curing period of a sample increases up to a maximum of 28 days. The thermal conductivity of the sample was found to be decreased as the POBA replacement increases. In conclusion, an eco-friendly concrete blend from palm oil boiler ash provides a potential alternative in converting industrial waste to beneficial building and construction material. The use of ECO-BAC in the construction sector can lead to a green structure while reducing the material costs and waste materials from industries. This project will drive to the development of POBA-foamed concrete, which possesses a lightweight characteristic and substantially a favourable compressive strength.